Profissionalização do trabalho docente : o novo Plano de Cargos, Carreira e Vencimentos da Educação do município de Rondonópolis-MT - Ferreira, Isabel Cavalcante (2019)
This research deals with the profound transformations that have taken place in the contemporary world of work, from the productive restructuring under the logic of neoliberalism, globalization and the flexible accumulation of capital, technological, cultural, social, political and economic changes that have affected professional life and staff of the teaching staff. These changes, is given by managerial elements such as: flexibilization and deregulation of laws, precariousness and proletarianization of work, in the neoliberal system, require and impose new performances on the worker / teacher, demanding from them the unbridled search for qualification and professional requalification, as a condition to improve the remuneration, permanence and competition in the labor market. What to a certain extent the reforms of the policies that are being implemented in Brazil for the professionalisation of teaching work, therefore, reshape and alter the objectives, functions and organization in the field of education and, consequently, in the field of regulation of the profession and teaching career. In this study, we have a guiding question: What is the contributions and implications of the Job Careers and Salaries Plan for professionalization of the teaching work of the municipal teaching network of Rondonópolis-MT? We think about that, because the professionalization of teaching work is an intention of capitalist global society in constant discussion in the public and economic policies of Latin America through the international organizations [ILO, UNESCO]. The idea of career as an indicator of professionalism for professional appreciation, attractiveness and professionalism of the teaching worker, in the current context of the contemporary work world is linked to the factors initial training in the academy, vocational courses for the achievement of a profession and occupational position in the labor market. Thus, this study is a qualitative research based on the methodological assumptions of dialectical historical materialism. For the dialectical whole clarifies that the work of teaching in its constitution is a living work, full of subjectivity, largely social. The objective of this research is to discuss the Process of Regulation of Teaching Work of the Municipal Education Network based on the Analysis of the Career Plan, Career and Education Salaries of the Municipality of RondonópolisMT - PCCV - Law 228 of March 28, 2016, and the implications of professionalization of teaching work in the web of class relations, reproduction, social relations and reinvention of capitalism in its crisis periods. In this sense, we observe from the analysis of the semistructured interviews the resistance and contestation, domination and oppression in the dispute process for the restructuring of the previous Career Plan, Careers and Education Wages - PCCS - Law 003/2000. Analyzes indicated that the teaching profession in the PCCV, appears in the academic formations required to enter the teaching career, in the permanent and post-graduation courses in order to professionalize.